The Laws of Texas 1822-1897. Austin’s Colonization Law and Contract; Mexican Constitution of 1824; Federal Colonization Law; Colonization Laws of Coahuila and Texas; Colonization Law of State of Tamaulipas; Fredonian Declaration of Indpendence; Laws and Decrees, with Constitution of Coahuila and Texas; San Felipe Convention; Journals of the Consultation; Proceedings of the General Council; Goliad Declaration of Independence; Journals of the Convention at Washington; Ordinances and Decrees of the Consultation; Declaration of Independence; Constitution of the Republic; Laws, General and Special, of the Republic; Annexation Resolution of the United States; Ratification of the Same by Texas; Constitution of the United States; Constitutions of the State of Texas, with All the Laws, General and Special, Passed Thereunder, Including Ordinances, Decrees, and Resolutions, with the Constitution of the Confederate States and the Reconstruction Acts of Congress, at 234-235, ch. 118, art. 10 (Vol. 6, 1898) - (:unkn) unknown (General Publisher, 1898)
That from and after the passage of this act it shall be unlawful to fire any pistol, rifle, shot gun, or other kind of fire-arms, within the limits of the town of Round Top, and any person violating this act shall be guilty of a misdemeanor,
--
Keywords: DISCHARGE